2007
DOI: 10.1007/s11205-007-9221-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Item Functioning of a Family Affluence Scale: Validation Study on Data from HBSC 2001/02

Abstract: Family affluence scale, Differential item functioning, Health Behaviour in School-aged Children (HBSC), Comparability, Validity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 25 publications
9
88
1
2
Order By: Relevance
“…Concerning the reliability of FAS II, in our study, the internal correlations between the FAS II items were low but all items were intercorrelated (r s = 0.16-0.39, p < 0.001) and the Cronbach's alpha was moderate (0.58), which is in line with previous studies (Cho and Khang 2010;Lin 2011;Molcho et al 2007;Schnohr et al 2008). These results were understandable due to the limited range of the alternatives and each item describing a different aspect of family affluence (Wardle et al 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning the reliability of FAS II, in our study, the internal correlations between the FAS II items were low but all items were intercorrelated (r s = 0.16-0.39, p < 0.001) and the Cronbach's alpha was moderate (0.58), which is in line with previous studies (Cho and Khang 2010;Lin 2011;Molcho et al 2007;Schnohr et al 2008). These results were understandable due to the limited range of the alternatives and each item describing a different aspect of family affluence (Wardle et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the item-rest coefficients in our study concluded that if the item on own bedroom was deleted from the FAS scale, the alpha coefficient would improve whereas deleting any other of the three items would reduce the internal consistency. Those findings suggested that further examination should be considered to choose the most sensitive items in specific settings since country and culture difference may affect the relative contribution of the four FAS II items to the composite FAS II (Schnohr et al 2008). One extra item which may be considered and tested in the future is that to ask the amount of weekly pocket money received by the student, which the child will reliably know the answer to, and is related to family affluence to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…School-based samples might lead to underestimation of the social inequality in health, which is a potential explanation for the finding of no association between FAS and health complaints in four countries with relatively low GNP. c) Validity of the outcome measure: The available studies suggest that the data on health complaints have an acceptable reliability and validity [36][37][38][39] 58 and Batista-Foguet et al 59 have shown that FAS is not completely comparable across countries because the individual items have different importance in different countries. The distribution of the study populations across the three FAS groups, high, medium and low, also varies across countries.…”
Section: Discussionmentioning
confidence: 99%
“…17 Immigrant status was determined by asking a student the country in which they were born and how long they had lived in Canada. Data corresponding to these items were categorized into Born in Canada; immigrant >5 years; or immigrant ≤5 years.…”
Section: Study Variablesmentioning
confidence: 99%